2005
DOI: 10.1136/oem.2004.015107
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traffic exhausts and oxidative DNA damage

Abstract: Aims: To assess the relations between exposure to traffic exhausts and indicators of oxidative DNA damage among highway toll station workers. Methods: Cross-sectional study of 47 female highway toll station workers exposed to traffic exhausts and 27 female office workers as a reference group. Exposure assessment was based on average and cumulative traffic density and a biomarker of exposure, urinary 1-hydroxypyrene-glucuronide (1-OHPG). Urinary 8-hydroxydeoxyguanosine (8-OHdG) was used as a biomarker of oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 26 publications
(28 reference statements)
1
57
1
Order By: Relevance
“…A major product with a clear mutagenic potential, deoxyguanosine (dG) in urine, has been commonly used as a biomarker of oxidative stress in studies on ambient air pollution (7)(8)(9)(10). Conversely, urinary 1-hydroxypyrene-glucuronide (1-OHPG), a PAH metabolite, has been used as a biomarker of exposure to PAHs (9,11,12). Urinary metals, including cadmium (Cd), arsenic (As), nickel (Ni), lead (Pb), and copper (Cu), indicate short-term or long-term levels of internal dose of exposure to metals (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major product with a clear mutagenic potential, deoxyguanosine (dG) in urine, has been commonly used as a biomarker of oxidative stress in studies on ambient air pollution (7)(8)(9)(10). Conversely, urinary 1-hydroxypyrene-glucuronide (1-OHPG), a PAH metabolite, has been used as a biomarker of exposure to PAHs (9,11,12). Urinary metals, including cadmium (Cd), arsenic (As), nickel (Ni), lead (Pb), and copper (Cu), indicate short-term or long-term levels of internal dose of exposure to metals (13).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary metals, including cadmium (Cd), arsenic (As), nickel (Ni), lead (Pb), and copper (Cu), indicate short-term or long-term levels of internal dose of exposure to metals (13). Most studies showed that exposure to either PAHs or metals could increase levels of urinary 8-oxodG in occupational or environmental fields (7)(8)(9)14). Only a few studies have investigated the effect of their interaction on biomarkers of oxidative stress, but a joint effect between PAHs and metals was not found (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no significant difference in adjusted 8-OHdG levels between the MBOCA-exposed and unexposed groups, this study found that a male gender, a history of smoking, and being older were associated with increased plasma 8-OHdG. The risk factors which have been shown to be associated with elevation of 8-OHdG includes age, gender, smoking, and other lifestyle factors [19][20][21][22][23][24][25] . Our findings were consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We recently studied toll workers exposed to high levels of PM 2.5 from traffic exhausts and found elevated levels of urinary 8-hydroxydeoxyguanosine (8-OHdG), a biomarker of oxidative DNA damage, and plasma NO compared with unexposed subjects (Lai et al, 2005). We also measured urinary 1-hydroxypyrene-glucuronide (1-OHPG) as a biomarker of PAH exposure and found a statistically significant association between the biomarker of exposure (1-OHPG) and oxidative DNA damage (8-OHdG) (Lai et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%